Decal Ni mesh to enhance the conductivity of carbon back contacts in dye sensitized and perovskite solar cells - Jorge Martins (2024)
Dye-sensitized solar cells (DSSCs) and perovskite solar cells (PSCs) are photovoltaic (PV) technologies that originally utilized precious metals like gold, silver, and platinum as counter-electrodes. Carbon materials are a low-cost alternative to traditional metal counter-electrodes in monolithic-DSSCs (M-DSSCs) and PSCs. However, the drawback of carbon-based counter-electrodes is that they often show a low electronic conductivity, which hinders the scale-up of these PV technologies. This study proposes using decal Ni-mesh produced through simple and scalable photolithography-assisted electroplating. The Ni-mesh is incorporated into the carbon layer to improve the counter-electrode conductivity in large-area M-DSSCs and PSCs. Carbon-counter electrodes embedded with Ni-mesh enhance the performance of M-DSSCs and PSCs by 132% and 41%, respectively. Impedance spectroscopy study shows that the embedded Ni-mesh effectively reduces the series resistance of the devices by half, leading to an enhancement in their overall performance. Decal of a nickel mesh prepared by photolithography-assisted electroplating on carbon counter-electrode of dye sensitized and perovskite solar cells improves the conductivity of the back contact and the performance of the devices.